Influence of Academic Leadership on the Effectiveness of School Under Khon Kaen Primary Educational Service Area Office 5 - Daungkhamdee, Munthita; Prasertphorn, Vanich (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were 1) to study academic leadership of school administrators under Khon Kaen Primary Educational Service Area Office 5, 2) to study the effectiveness of schools under Khon Kaen Primary Educational Service Area Office 5, and 3) to study the relationship between academic leadership of school administrators and the effectiveness of schools under Khon Kaen Primary Educational Service Area Office 5. The sample group used in the research consisted of 33 school administrators and 304 teachers, with the total number of 337 people. The sample size was determined by Taro Yamane’s formula at a sampling error level of .05 using cluster random sampling method. The instrument used to collect data was a 5-level rating scale questionnaire on academic leadership of school administrators with reliability of 0.98 and the effectiveness of schools with reliability of 0.98. The statistics used to analyze data comprised frequency, percentage, mean, standard deviation, and Pearson’s product moment Correlation Coefficient. The research results were found that: 1) Academic leadership of school administrators, in overall and each aspect, was rated at a high level. 2) The effectiveness of schools under Khon Kaen Primary Educational Service Area Office 5, in overall and each aspect, was rated at a high level. 3)The relationship between academic leadership of school administrators and the effectiveness of schools under Khon Kaen Primary Educational Service Area Office 5 were found that the relationship was related at the highest level.